Use of STOP-BANG Questionnaire to Predict Postoperative Respiratory Complications after Bariatric Surgery - Sezari, Parisa; Safari, Farhad; Mottaghi, Kamran; Asgari, Sogol; Parto, Sepideh; Salimi, Alireza; Nashibi, Masoud (Tanaffus, 2024)
Obstructive sleep apnea (OSA) is the most common sleep-related breathing disorder associated with multisystem organ involvement. The STOP-BANG questionnaire is a short and valid questionnaire used to screen OSA. This study aimed to investigate the ability of the STOP-BANG questionnaire to predict postoperative OSA- related respiratory complications in patients undergoing bariatric surgery. In this cross-sectional study, all the eligible patients were evaluated in preoperative visits using a predetermined checklist including demographic and clinical information related to OSA and the STOP-BANG questionnaire. After bariatric surgery, patients were assessed for postoperative OSA-related complications. The receiver operating characteristic (ROC) curve was used to determine the cut-off point of the STOP-BANG checklist score based on the patient's postoperative outcomes. In total, 115 subjects were included in the study. There were significant associations in terms of gender, age, body mass index (BMI), patient's neck circumference, diabetes, heart diseases, and the mask ventilation grade variables between the two groups of patients with high risk and low risk according to the STOP-BANG questionnaire (P < 0.05 for all comparisons). In addition, ai rway obstruction and hypoxia (mild and moderate) were more prevalent in the high-risk group than in the low-risk one (P < 0.05 for all comparisons). A significant difference was reported with a cut-off score of 2 in the STOP-BANG questionnaire for those with and without airway obstruction. Moreover, the cut-off point of 4 in the STOP-BANG questionnaire was determined as a predictor for both airway obstruction and mild-to-moderate hypoxia. STOP- BANG scores may be used as a preoperative risk stratification tool to predict the risk of intraoperative adverse events and postoperative complications in bariatric surgery.